Western Australian Aboriginal young women and community representatives identify barriers to school attendance and solutions to school non-attendance - Whitau, Rose; Bolton-Black, Latoya; Ockerby, Helen; Corley, Lowana (The Australian Journal of Indigenous Education, 2022)
The barriers to school attendance that affect young Aboriginal people in Australia are diverse, immense and well documented; however, except for a handful of studies, Aboriginal students’ voices receive no platform for policy makers to hear them. In this paper, we present results from yarning circles about barriers to school attendance conducted with young Aboriginal women that participate in an education engagement program called Shooting Stars at Narrogin Senior High School. Yarning circles were facilitated, analysed and discussed within a framework of relatedness, with the researchers embracing their own standpoint, and the standpoint of the Shooting Stars participants, as Indigenous women. The results from these participant yarning circles were discussed with the Shooting Stars Narrogin localised steering committee, and this discussion is presented here, alongside the outcomes, both achieved and projected, to which committee stakeholders have committed. For the most part, the participants and the steering committee discussed racism, teacher–student relationships, and peer connectedness, and how these were related to participant attendance and engagement at school. This paper showcases the power of the yarning circle as a tool for collaboration in that it provides a space to create cohesion through conversation, through contention and through sharing.